Changes of infants’ motor development using corrective education - Mockevičienė, Daiva; Miliūnienė, Lina (Social Welfare: Interdisciplinary Approach, 2011)
The article deals with the research, the goal of which is stating the effect of corrective education on the impaired motor development of infants depending on the beginning of corrective education. In order to assess the motor development of infants the Munich functional development diagnostics was used. There participated 120 infants attending early rehabilitation service of Šiauliai consulting policlinics for children’s disease clinics. The fi rst assessment of the complex motions of infants was made in different age groups (group I – 3±0,5 months; group II – 6±0,5 months). Generalizing information in scientifi c literature about the results of evaluation of children’s motor development in different periods until the age of one who had undergone neurodynamic therapy (NDT) and taking into consideration the results of our research we can say that the essential factor deciding the success of early intervention is infant’s age at the beginning of corrective education. If complex correction begins earlier then it causes better results of psychomotor development.
Keywords: infants’ motor development; corrective education; neurodynamic therapy (NDT)